Fred D. Guker, ed., Revised Ordinances of the City of Red Bud, Randolph Co., Illinois (Red Bud, IL: Seely Pilgrim, 1898), 35. Article 3—Public Safety, §8—Selling Weapons to Minors. Passed March 1, 1898, & Published March 29, 1898 - (:unkn) unknown (General Publisher, 1898)
Prohibited selling, giving, loaning, hiring, bartering, any minor a revolver, gun, derringer, slung shot, cross knuckles, knuckles of lead, brass, or other metal, Bowie-knife, dirk, dagger, or any other dangerous or deadly weapon. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER - MINORS